Analysis of a full-memory multidestination ARQ protocol over broadcast links. - Jianhua He
Based on an assumption that a steady state exists in the full-memory multidestination automatic repeat request (ARQ) scheme, we propose a novel analytical method called steady-state function method (SSFM), to evaluate the performance of the scheme with any size of receiver buffer. For a wide range of system parameters, SSFM has higher accuracy on throughput estimation as compared to the conventional analytical methods
Keywords: ARQ protocol; Analytical method; Automatic repeat request; Broadcast links; Full-memory multidestination protocol; Receiver buffer; Steady-state function method; Throughput estimation